An appraisal on the obligation of companies to pay zakat: The Malaysian law and shariah perspectives - Zuhairah Ariff, Abd Ghadas; Nazri, Ramli (2018)
Zakat is one of the five pillars of Islam obligatory upon human beings who believe in Allah and His Messenger (pbuh). It refers to the determined share of wealth prescribed by Allah as an act of worship. The consideration of its great objectives (al-maqasid) in Islam, among others, public interest and social justice to the Muslim society influences contemporary Muslim jurists to uphold the obligation of companies to pay zakat as issued in their fatwas and resolutions. In Malaysia, several fatwas and resolutions issued by the religious fatwa councils clearly impose this religious obligation on the corporations as their business zakat (urudh altijarah) which are legally registered under the Companies Act 2016. This paper discusses the obligation of companies to pay zakat from Malaysian law and Shariah perspectives. It aims to analyse whether it is legally viable for corporations registered under the Companies Act 2016 which adopts the English common law to be obligated to pay zakat. Research methodology applied in this paper is doctrinal and statutory analysis.